Baltic Botanic Gardens in 2015-2017 - Tomsone, Signe (University of Latvia, 2019)
The periodical issue of Baltic Botanic Gardens includes information about the main events in the botanical gardens of Estonia, Latvia and Lithuania in 2015-2017. It contains statistical information about the gardens and the articles about plant collections, research and public activities.
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology; botanical garden; botany; plant collection